(untitled) (Journal of Foreign Language Studies, 2024)
Cognitive linguistics is an interdisciplinary branch of linguistics that studies language on the basis of human experience and perceptions of the objective world. Nowadays, issues related to cognitive linguistics have attracted much attention from many researchers. This article presents some basic concepts in cognitive linguistics, such as category, categorization and prototype. It then points out similarities and differences between adjectives in Japanese and Vietnamese language as well as factors forming prototypes of this category in the two languages.